Air–Water Interfacial Directed Self‐Assembly of Block Copolymer Nanostrand Array. Issue 20 (16th June 2022) - Kim, Dong Hyup; Kim, So Youn
Abstract: Interfacial self‐assembly (ISA) of block copolymers (BCPs) creates various periodic 2D nanostructures at the air–water interface, such as dot, strand, and planar morphologies, which are widely used in various applications. Here, a directed self‐assembly strategy to control the pattern direction of ISA of strand morphology, so‐called nanostrands, in a large area using a gradual morphology transition is introduced. ISA of BCPs in a lens‐shaped droplet of a concentrated BCP solution at the air–water interface shows the gradual morphology transition from the edge to the center of the droplet. The gradual morphology transition is explained by the spreading area‐dependent dewetting mechanism. Furthermore, a dense nanostrand array in a large area which is highly aligned normal to the radial direction of the droplet at an intermediate transition regime is found. In addition, a density‐doubled metal nanowire fabrication and a hierarchical BCP nanopatterning by using the highly aligned nanostrand array as a template are demonstrated. Abstract : Interfacial self‐assembly (ISA) of block copolymers (BCPs) creates periodic 2D nanostrands at the air–water interface. This study introduces a directed self‐assembly strategy for BCP nanostrands. A gradual morphology transition of ISA produces an aligned nanostrand array in a large area. A density‐doubled metal nanowire fabrication and a hierarchical BCP nanopatterning are demonstrated based on highly aligned nanostrand array templates.